APPLICATION OF NEW INNOVATIVE METHODS IN CARDIAC SURGERY - Abdurasulova Y.Sh; Rahmatov B.Sh; Khudayberganova N.Kh (Scholar Express Journals, 2025)
Over the past decades, cardiac surgery has become one of the most innovative fields in modern medicine. As cardiovascular diseases remain among the leading causes of death worldwide, there is a growing need to improve surgical techniques and enhance safety levels [3]. In contemporary cardiac surgery, minimally invasive, robot-assisted, transcatheter, and mechanical assistive technologies are being widely implemented.
Keywords: Cardiac surgery; minimally invasive; robotic surgery